Political by design the Mandaluyong City Government Center - Padios, Raphael Enrique S.
The city of Mandaluyong, located at the core of the Metropolitan Manila region, is tagged as one of the fastest growing cities in the region. This growth elicits a new need for proactive building, specifically creating spaces for urbane activities, welfare enhancement, service administration, and civic participation. Apart from these, the city government would also benefit from a recognizable sense of place -- a place that is the primary reference for the city of Mandaluyong. The site poses a distinct problem of organization. With the rapid urban development taking over the region, there is a need for the government to respond and prepare to meet this growth with its own. The conditions of the site also poses systemic issues not particularly distinct to the city. A common theme among interviews of the city officials is discipline and the lack thereof across different activities; Traffic Management Systems, Green Building Codes, and Public Open Spaces cannot be properly utilized by an uninvolved, uninformed, and un-empowered citizenship. There lies the cusp of what the redevelopment plan is for, to suggest that the vision of a progressive, functional, and efficient city is indeed true, good, and beautiful, that the democratic elements of governance function only when there is will, and that the building be a testament to the government's commitment to all people. It is through the development of a narrative within a designed environment that we can show that discipline and order do go with progress. To achieve a design that is capable of communicating this narrative, there needs to be a concept linking the design agenda to the project rationale. At the very core of the goal of the incumbent City Government is the thrust for community collaboration and unity. And the design can achieve this by invoking an established identity of the city of Mandaluyong : Home. This is used by numerous historic groups to refer to the City. This identity, aside from being well established in the subconscious of the local community, is as much about emotion (feeling) as it is about spatial characteristics (look), Making it an ideal concept to tie the project together. The proposed project is the conceptualization of the redevelopment of the Mandaluyong City Government Center in Maysilo Circle, Barangay Plainview. The project aims to tackle issues of traffic gridlock and the lack of open space and imageability in the area through urban design and architecture interventions. The study presents a narrative of how architecture incorporate key concepts and respond to the context of Mandaluyong City.